Answer:
The following pairs/results are matched:
= ![\frac{16t}{3}-\frac{23}{5}](https://tex.z-dn.net/?f=%5Cfrac%7B16t%7D%7B3%7D-%5Cfrac%7B23%7D%7B5%7D)
= ![-\frac{11}{4}t+36](https://tex.z-dn.net/?f=-%5Cfrac%7B11%7D%7B4%7Dt%2B36)
Step-by-step explanation:
Lets solve all the expressions to match the results.
<em>Solving the expression</em>
![5\left(2t+1\right)+\left(-7t+28\right)](https://tex.z-dn.net/?f=5%5Cleft%282t%2B1%5Cright%29%2B%5Cleft%28-7t%2B28%5Cright%29)
![\mathrm{Remove\:parentheses}:\quad \left(-a\right)=-a](https://tex.z-dn.net/?f=%5Cmathrm%7BRemove%5C%3Aparentheses%7D%3A%5Cquad%20%5Cleft%28-a%5Cright%29%3D-a)
![5\left(2t+1\right)-7t+28](https://tex.z-dn.net/?f=5%5Cleft%282t%2B1%5Cright%29-7t%2B28)
![10t+5-7t+28](https://tex.z-dn.net/?f=10t%2B5-7t%2B28)
![3t+33](https://tex.z-dn.net/?f=3t%2B33)
Therefore,
= ![3t+33](https://tex.z-dn.net/?f=3t%2B33)
<em>Solving the expression</em>
![3\left(3t-4\right)-\left(2t+10\right)](https://tex.z-dn.net/?f=3%5Cleft%283t-4%5Cright%29-%5Cleft%282t%2B10%5Cright%29)
![9t-12-\left(2t+10\right)](https://tex.z-dn.net/?f=9t-12-%5Cleft%282t%2B10%5Cright%29)
![9t-12-2t-10](https://tex.z-dn.net/?f=9t-12-2t-10)
![7t-22](https://tex.z-dn.net/?f=7t-22)
Therefore,
= ![7t-22](https://tex.z-dn.net/?f=7t-22)
<em>Solving the expression</em>
![\left(4t-\frac{8}{5}\right)-\left(3-\frac{4}{3}t\right)](https://tex.z-dn.net/?f=%5Cleft%284t-%5Cfrac%7B8%7D%7B5%7D%5Cright%29-%5Cleft%283-%5Cfrac%7B4%7D%7B3%7Dt%5Cright%29)
![\mathrm{Remove\:parentheses}:\quad \left(a\right)=a](https://tex.z-dn.net/?f=%5Cmathrm%7BRemove%5C%3Aparentheses%7D%3A%5Cquad%20%5Cleft%28a%5Cright%29%3Da)
![4t-\frac{8}{5}-\left(3-\frac{4}{3}t\right)](https://tex.z-dn.net/?f=4t-%5Cfrac%7B8%7D%7B5%7D-%5Cleft%283-%5Cfrac%7B4%7D%7B3%7Dt%5Cright%29)
![4t-\frac{8}{5}-\left(-\frac{4t}{3}+3\right)](https://tex.z-dn.net/?f=4t-%5Cfrac%7B8%7D%7B5%7D-%5Cleft%28-%5Cfrac%7B4t%7D%7B3%7D%2B3%5Cright%29)
![4t-\frac{8}{5}-3+\frac{4t}{3}](https://tex.z-dn.net/?f=4t-%5Cfrac%7B8%7D%7B5%7D-3%2B%5Cfrac%7B4t%7D%7B3%7D)
As
and ![\frac{4t}{3}+4t:\quad \frac{16t}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B4t%7D%7B3%7D%2B4t%3A%5Cquad%20%5Cfrac%7B16t%7D%7B3%7D)
So,
will become ![\frac{16t}{3}-\frac{23}{5}](https://tex.z-dn.net/?f=%5Cfrac%7B16t%7D%7B3%7D-%5Cfrac%7B23%7D%7B5%7D)
Therefore,
= ![\frac{16t}{3}-\frac{23}{5}](https://tex.z-dn.net/?f=%5Cfrac%7B16t%7D%7B3%7D-%5Cfrac%7B23%7D%7B5%7D)
<em>Solving the expression</em>
![\left(-\frac{9}{2}t+3\right)+\left(\frac{7}{4}t+33\right)](https://tex.z-dn.net/?f=%5Cleft%28-%5Cfrac%7B9%7D%7B2%7Dt%2B3%5Cright%29%2B%5Cleft%28%5Cfrac%7B7%7D%7B4%7Dt%2B33%5Cright%29)
![\mathrm{Remove\:parentheses}:\quad \left(a\right)=a](https://tex.z-dn.net/?f=%5Cmathrm%7BRemove%5C%3Aparentheses%7D%3A%5Cquad%20%5Cleft%28a%5Cright%29%3Da)
![-\frac{9}{2}t+3+\frac{7}{4}t+33](https://tex.z-dn.net/?f=-%5Cfrac%7B9%7D%7B2%7Dt%2B3%2B%5Cfrac%7B7%7D%7B4%7Dt%2B33)
![\mathrm{Group\:like\:terms}](https://tex.z-dn.net/?f=%5Cmathrm%7BGroup%5C%3Alike%5C%3Aterms%7D)
![\frac{9}{2}t+\frac{7}{4}t+3+33](https://tex.z-dn.net/?f=%5Cfrac%7B9%7D%7B2%7Dt%2B%5Cfrac%7B7%7D%7B4%7Dt%2B3%2B33)
![\mathrm{Add\:similar\:elements:}\:-\frac{9}{2}t+\frac{7}{4}t=-\frac{11}{4}t](https://tex.z-dn.net/?f=%5Cmathrm%7BAdd%5C%3Asimilar%5C%3Aelements%3A%7D%5C%3A-%5Cfrac%7B9%7D%7B2%7Dt%2B%5Cfrac%7B7%7D%7B4%7Dt%3D-%5Cfrac%7B11%7D%7B4%7Dt)
![-\frac{11}{4}t+3+33](https://tex.z-dn.net/?f=-%5Cfrac%7B11%7D%7B4%7Dt%2B3%2B33)
![-\frac{11}{4}t+36](https://tex.z-dn.net/?f=-%5Cfrac%7B11%7D%7B4%7Dt%2B36)
Therefore,
= ![-\frac{11}{4}t+36](https://tex.z-dn.net/?f=-%5Cfrac%7B11%7D%7B4%7Dt%2B36)
Thus, the following pairs/results are matched:
= ![\frac{16t}{3}-\frac{23}{5}](https://tex.z-dn.net/?f=%5Cfrac%7B16t%7D%7B3%7D-%5Cfrac%7B23%7D%7B5%7D)
= ![-\frac{11}{4}t+36](https://tex.z-dn.net/?f=-%5Cfrac%7B11%7D%7B4%7Dt%2B36)
Keywords: algebraic expression
Learn more about algebraic expression from brainly.com/question/11336599
#learnwithBrainly
Answer:
- Their rate was 85 toys per day.
Step-by-step explanation:
<u>Given equation:</u>
<u>Now, let's solve the equation:</u>
Their rate was 85 toys per day.
The answer is $18. Put the 38 in the place of b, b being the amount of times someone rides the bus. Hence, C=0.25(38) + 8.50. Then, multiply the multiplable numbers. You get 9.5. Add 9.5 and 8.50 to get 18.
Answer:
b=12
Step-by-step explanation:
To solve the equation, you need to isolate/get the variable "P" by itself in the equation:
P - 3 = -4 Add 3 on both sides to get "P" by itself
P - 3 + 3 = -4 + 3
P = -1
PROOF
P - 3 = -4 Plug in -1 for P
-1 - 3 = -4
-4 = -4